Probing the effects of oxygen-related defects on the optical and luminescence properties in CaCu3Ti4O12 ceramics - Felix, A. A. [UNESP]; Spreitzer, M.; Vengust, D.; Suvorov, D.; Orlandi, M. O. [UNESP] (Elsevier, 2018)
The formation of oxygen-related lattice defects and their influence on optical and electronic properties in CaCu3Ti4O12 (CCTO) ceramics were studied by controlling the oxygen partial pressure during the sintering process at high temperatures. The samples were analyzed using complementary bulk spectroscopic techniques such as photoluminescence spectroscopy, ultraviolet-visible spectroscopy, Fourier-transform infrared spectroscopy, and electron paramagnetic resonance. Our comprehensive study shows that the oxygen content during sintering process exerts considerable control over the type and concentration of oxygen-related defects in the crystalline CCTO structure. Our results also suggest that the formation of different types of oxygen-related defects in the structure modifies electronic energy levels and thus directly affects the electronic and optical properties of the CCTO phase. These results provided further insight into the important role of oxygen in the crystalline defect arrangement in polycrystalline CCTO ceramics.
Keywords: CaCu3Ti4O12; Defects; Electronic structure; Oxygen; Spectroscopic techniques